A study on the contribution of supply chain management to Ghana's rice industry - Abdul Raheed, Fasasi (2012)
The cropping system in Ghana is generally characterized by low productivity especially rice and as such efforts have been made by stakeholders in the industry to address this phenomenon. This development has therefore generated a persistent gab between the supply side of locally cultivated rice and the demand side of it. The system is also characterized by low level of technology and productivity, low income and un-competitiveness in production, processing and distribution hence a weak linkage between production areas and the market largely due to supply chain problems. Other challenges associated with the rice supply chain system are low inventory levels, inadequate facilities, poor road infrastructure leading to post-harvest losses, inadequate investment in irrigation, logistics, lack of information on best farming practices and market trends. The impact of these hiccups in the rice industry is low level of rice production on a yearly basis. This therefore leads to huge rice imports. To boost rice production, this study employed the six drivers of supply chain management (inventory, transportation, pricing, sourcing, information and facilities) and assessed how each would contribute to the performance of the rice industry in terms of quantity. This study was on the contribution of supply chain management to Ghana's rice industry.